2001
DOI: 10.1038/sj.ijo.0801814
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orlistat on weight and on serum lipids in obese patients with hypercholesterolemia: a randomized, double-blind, placebo-controlled, multicentre study

Abstract: OBJECTIVE: Assessment of the effects of orlistat 120 mg three times daily vs placebo on weight loss and serum lipids in obese hypercholesterolemic patients. DESIGN: A 24 week multicentre, double-blind, randomized, placebo-controlled trial. After a 2-week single-blind run-in period (placebo þ diet (7600 kcal=day; 30% of calories as fat)), 294 patients were submitted to the hypocaloric diet and randomly assigned to either orlistat 120 mg or placebo three times daily. Patients who completed the double-blind study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 21 publications
11
80
1
9
Order By: Relevance
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…To help put these data in context, placebocontrolled studies of some FDAapproved weight loss pharmacotherapies have reported losses 2.7 to 4.5 kg greater than losses with placebo over 6 to 12 months for patients taking sibutramine [43][44][45][46] or orlistat [47][48][49][50][51] ; or 7.2 kg greater than with placebo at 9 months for patients taking phentermine. 52 There are no data regarding weight loss beyond 6 months' use of ephedrine or ephedra.…”
Section: Commentmentioning
confidence: 99%
“…In adults, orlistat at the standard dose, 120 mg TID, inhibits approximately 30% of triglyceride absorption 15 with few adverse effects 17 . In placebocontrolled studies, adults treated with orlistat for periods as long as 2 years exhibited greater average weight loss, better weight maintenance, lower total and LDL cholesterol, and, in those with type 2 diabetes, improved glycemic control [16][17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%